The influence of advanced maternal age on congenital malformations, short- and long-term outcomes in offspring of nulligravida: a Korean National Cohort Study over 15 years - Su Jin You; Danbee Kang; Ji-Hee Sung; Hyejeong Park; Juhee Cho; Suk-Joo Choi; Soo-Young Oh; Cheong-Rae Roh (Korean Society of Obstetrics and Gynecology, 2024)
Objective To assess the influence of advanced maternal age on congenital malformations, short- and long-term outcomes in offspring of nulligravida. Methods A retrospective study was conducted using the Korean National Health Insurance Service database spanning from January 2005 to December 2019. All live-born offspring of nulligravida (n=3,685,817) were included. The maternal age was subdivided into the following subgroups: <25 years (n=153,818), 25-29 years (n=845,355), 30-34 years (n=1,738,299), 35-39 years (n=787,530), 40-44 years (n=151,519), and >44 years (n=9,296). Outcomes were assessed based on International Classification of Diseases-10 codes. Adjusted odds ratios (aOR) were calculated with the group of 25-29 years as a reference. Result Most congenital malformations showed an age dependent increase, but cleft lip and abdominal wall defect exhibited a U-shape curve, indicating an increase even in those <25 years old. Similarly, various disorders included in the neonatal composite outcomes from short-term outcomes showed aged dependent escalation. However, the preterm birth from the short-term outcome and most of the long-term developmental outcomes, except for motor developmental delay and Tics, showed a U-shaped pattern. The aOR of autism and cerebral palsy, showing the most obvious U-shaped curved in the long-term outcomes, was 1.50 (95% confidence interval [CI], 1.24-1.82) and 1.54 (95% CI, 1.17-2.03), respectively in the group >44 years old and 1.18 (95% CI, 1.11-1.25) and 1.19 (95% CI, 1.09-1.30) in <25 years old group. Conclusion Overall, an advanced maternal age has an age-dependent correlation with most congenital malformations and shortand long-term outcomes of neonates.